Determination of trace metal levels of Cd, Pb, Cr, Ni, and Cu in Two Fish Species by STAT-AAS and ICP-AES - Yaman, Mehmet; Yaman, Ibrahim H. (My University, 2013)
The concentrations of five toxic metals (Cd, Pb, Cr, Ni, and Cu) were determined in two fish species, Scomber scombrus and Sparus auratus, obtained from fish markets in Turkish cities. For the determinations, slotted tube atom trap-atomic absorption spectrometry (STAT-AAS) and inductively coupled plasma atomic emission spctrometry (ICP-AES) were used. The obtained lead concentrations (mean 630 ?g kg1) for all Scomber scombrus samples were found to be higher than the maximum allowance concentrations (MAC) of 300 ?g kg1. Cadmium concentrations in both fish species (mean 90 ?g kg-1 for Scomber scombrus and 54 ?g kg-1 for Spams auratus) were found to be around the MAC values. The mean Cr, Ni, and Cu concentrations in Scomber scombrus were 313 ?g kg-1, 280 ?g kg-1, and 420 ?g kg-1, respectively. The same metal levels in Sparus auratus were 324 ?g kg-1 Pb, 268 ?g kg"1 Cr, 323 Mg kg-1 Ni, and 382 ?g kg -1 Cu. Although some metal concentrations exceed the limits set by the authorities, the estimated non-carcinogenic and carcinogenic health risks by the Target Hazard Quotient and target carcinogenic risk indicate that there are no sytemic effects, and the risk of developing cancer over a human lifetime is between 2-9 in 1,000,000. as "possibly carcinogenic to humans" (Group2B)(9).